2018
DOI: 10.1638/2017-0126.1
|View full text |Cite
|
Sign up to set email alerts
|

HEMATOLOGY, PLASMA BIOCHEMISTRY, AND URINALYSIS OF FREE-RANGING GREY-HEADED FLYING FOXES (PTEROPUS POLIOCEPHALUS) IN AUSTRALIA

Abstract: The grey-headed flying fox ( Pteropus poliocephalus) is a species endemic to coastal eastern Australia. This study presents a comprehensive set of biochemistry, hematology, and urinalysis biomarkers from which reference values were derived. Blood samples collected from free-ranging P. poliocephalus were submitted for hematology ( n = 140) and plasma biochemistry ( n = 161) and urine for urinalysis ( n = 95). The values for P. poliocephalus were broadly consistent with those values published for other Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…No basophils were observed in our sample set, which is consistent with the low numbers of basophils typically reported in mammals, including other flying fox species [ 22 , 24 , 28 , 30 , 31 ]. The average numbers of eosinophils and monocytes observed on the smears in our study were also consistent with what has been reported previously [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No basophils were observed in our sample set, which is consistent with the low numbers of basophils typically reported in mammals, including other flying fox species [ 22 , 24 , 28 , 30 , 31 ]. The average numbers of eosinophils and monocytes observed on the smears in our study were also consistent with what has been reported previously [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…hypomelanus) and Malaysian flying fox (P . vampyrus) were observed to be lymphocyte-dominant [ 28 – 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further haematological and biochemical differences have been found according to the sex and age categories in R. aegyptiacus , 19 P. alecto , 8 P. conspicillatus 6 and P. poliochephalus 9 but not in P. melanotus natalis . 10 The absence of differences observed in the present study may be due to the different statistical approach used.…”
Section: Discussionmentioning
confidence: 93%
“…4,5 They are also often kept in zoological parks in various countries. Although in the literature there are many studies on the laboratory data concerning Megachiroptera, 610 haematological and biochemical reference intervals (RIs) for Egyptian fruit bats are lacking. Although the serum protein electrophoresis of these animals may provide useful biological information it has not been evaluated before.…”
Section: Introductionmentioning
confidence: 99%
“…Age-dependent variations of hematological and biochemical parameters were observed in diverse bat species, with elevated levels of alkaline phosphatase and decreased levels of hemoglobin, hematocrit, as well as white and red blood cells in pre-mature animals being the most consistent findings ( Hall et al, 2014 ; McMichael et al, 2015 ; Edson et al, 2018 ; Olopade et al, 2020 ; Moretti et al, 2021 ). Additionally, although to a variable extent, different studies also reported sex-dependent characteristics such as higher white blood cells in females and higher alanine aminotransferase (ALT) values in males ( McLaughlin et al, 2007 ; Hall et al, 2014 ; McMichael et al, 2015 ; Edson et al, 2018 ). For the analysis and interpretation of data from hematology and clinical chemistry, it is of utmost importance to be aware of both age-, sex- and species-dependent variations.…”
Section: Introductionmentioning
confidence: 95%